2000
DOI: 10.1105/tpc.12.8.1393
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Calmodulin-Regulated Soybean Ca2+-ATPase (SCA1) That Is Located in the Plasma Membrane

Abstract: Ca 2 ؉ -ATPases are key regulators of Ca 2 ؉ ion efflux in all eukaryotes. Animal cells have two distinct families of Ca 2 ؉ pumps, with calmodulin-stimulated pumps (type IIB pumps) found exclusively at the plasma membrane. In plants, no equivalent type IIB pump located at the plasma membrane has been identified at the molecular level, although related isoforms have been identified in non-plasma membrane locations. Here, we identify a plant cDNA, designated SCA1 (for soybean Ca 2 ؉ -ATPase 1), that encodes Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…This is quite coherent also as fluctuations in the cytosolic calcium levels are one of the primary responses to various stimuli and Ca 2+ transport elements actively participate in maintaining this flux and homeostasis. Previously, it was reported that NaCl treatment leads to upregulation of the Ca 2+ ‐ATPase transcript level in different plant species such as tomato, tobacco, soybean and Arabidopsis and it was speculated that increased capacity of Ca 2+ ‐ATPase may help in lowering the cytosolic calcium level, which was elevated due to NaCl stress and might be involved in maintenance of Ca 2+ homeostasis. Also, overexpression of N‐terminal modified ACA4 in Arabidopsis seedlings resulted in increased salt tolerance in comparison with wild type plants .…”
Section: Discussionmentioning
confidence: 99%
“…This is quite coherent also as fluctuations in the cytosolic calcium levels are one of the primary responses to various stimuli and Ca 2+ transport elements actively participate in maintaining this flux and homeostasis. Previously, it was reported that NaCl treatment leads to upregulation of the Ca 2+ ‐ATPase transcript level in different plant species such as tomato, tobacco, soybean and Arabidopsis and it was speculated that increased capacity of Ca 2+ ‐ATPase may help in lowering the cytosolic calcium level, which was elevated due to NaCl stress and might be involved in maintenance of Ca 2+ homeostasis. Also, overexpression of N‐terminal modified ACA4 in Arabidopsis seedlings resulted in increased salt tolerance in comparison with wild type plants .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, despite its low expression level, ACA12 was able to complement the K616 phenotype, making it able to grow in the presence of 5 mM EGTA (Fig. 4), as only deregulated mutants of other ACA isoforms are able to do (Harper et al 1998; Chung et al 2000; Geisler et al 2000b; Hwang et al 2000; Sze et al 2000; Bonza et al 2004; Kabala and Klobus 2005; Schiøtt and Palmgren 2005; Baekgaard et al 2006; Lee et al 2007). Taken together, these results clearly indicate that ACA12 is a deregulated isoform of Arabidopsis type 2B Ca 2+ -ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the success of this method with the soybean Ca 2+ ‐ATPase SCA1 (Chung et al . ), an analogous region of CrACA1 was chosen for this expression. Primers were designed to amplify the A504‐V596 region of the gene (Table S1) for expression using a pETBlue bacterial expression vector to allow for His‐tag/Ni affinity purification.…”
Section: Methodsmentioning
confidence: 99%